Rancang Bangun Aplikasi Fast Parking System Berbasis Android Untuk Optimasi Alur Parkir di Kota Batam - Dodi Prima Resda; Destia Larasasti Tobing (STIKes Ibnu Sina Ajibarang, 2025)
The issue of illegal parking in Batam City has become a serious concern, where unofficial parking attendants often collect fees from drivers without contributing to the local government. This situation not only disrupts order and security but also harms local revenue (PAD). Illegal parking practices create discomfort for the public and reduce trust in the existing parking system. Moreover, it hinders the optimization of PAD potential that should be generated from a well-organized and orderly parking system. This research aims to develop a technological solution to address this issue by creating an Android application called Fast Parking System. The application is designed to improve parking system efficiency through a fast, secure, and transparent cashless payment system. By using this application, drivers can pay for parking digitally, reducing direct interaction with parking attendants and minimizing the potential for illegal fees. The application is also integrated with an official surveillance system, allowing local authorities to monitor parking activities in real-time and ensure that parking fees are directed to the local treasury. It is expected that the implementation of Fast Parking System will create a more orderly, safe, and efficient parking system. With this solution, the local government can not only increase transparency but also optimize revenue from the parking sector. In addition, the application offers greater convenience for the public in using well-managed parking facilities. The findings from this research can serve as a useful reference for the Batam City Government and other cities in Indonesia facing similar illegal parking issues. It can also be used as a guideline for developing more efficient and modern technology-based parking systems.